Accelerated thermal profiling of gas turbine components using luminescent thermal history paints. (25th April 2018) - Araguás Rodríguez, Silvia; Jelínek, Tomáš; Michálek, Jan; Yáñez González, Álvaro; Schulte, Fiona; Pilgrim, Christopher; Feist, Jorg; Skinner, Stephen J.
Abstract: Environmental requirements to reduce CO2 emissions and the drive towards higher efficiencies have resulted in increased operating temperatures in gas turbines. Subsequently, Original Equipment Manufacturer (OEMs) require improved component design and material selection to withstand the harsher conditions. This demands rapid evaluation of new components and their surface temperature to accelerate their market entry. Accurate temperature information proves key in the design of more efficient, longer-lasting machinery and in monitoring thermal damage. A number of traditional temperature measurement techniques are available, but can incur a number of limitations. Online temperature measurements, such as pyrometry or phosphor thermography, often require optical access to the component during operation and are therefore not suitable for inaccessible components. Other options including thermocouples can only provide point measurements and cannot deliver profiles across the surface. Offline techniques store temperature information that can be measured and analysed following operation. Several of these, however, are of destructive nature, can affect local thermal gradients and only provide point measurements. This article discusses an innovative offline measurement technique: luminescent Thermal History Paints (THPs). THPs are comprised of ceramic pigments in a binder matrix that can be applied to any hot component as a thin coating. These pigments are doped with optically active ions, which will phosphoresce when excited with a light source. The coating material experiences irreversible structural changes depending on the temperature it is exposed to. Changes in the material structure are reflected in its phosphorescent properties, which are measured with standard optical instrumentation at any surface location. Since the changes are permanent, the temperature information is stored in the coating and can be extracted after operation. Following calibration, it is therefore possible to relate phosphorescent behaviour to the past maximum temperature experienced at each location. This is done with Sensor Coating Systems Ltd. (SCS)'s portable instrumentation, which can provide rapid, automated and objective measurements across a component surface. Unlike the more traditional thermal paints, THPs are non-toxic, and provide a continuous measurement capability across the range 150°C–900°C with significantly improved durability. This article describes the underlying principles behind this novel technology and the advantages it provides over existing state-of-the-art methods. The benefits will be demonstrated through measurements on nozzle guide vanes (NGVs), with the view to compare and validate them against thermocouple measurements. The results show that the THP extends the limited information from thermocouples to provide a more complete view of the thermal processes on the component.